PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN DALAM MENJALANKAN UMKM ALOSTEIN STORE - Egi Irawan; Novan Aziz Ramadhan; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (Cross-border, 2023)
Micro, Small and Medium Enterprises (UMKM) is a small business unit that functions as a safety valve both in providing alternative productive business activities, alternative credit distribution, as well as in terms of employment and becoming a creative economic force in Indonesia. Pedes is one of the areas that is used as a creative economic center for the Karawang region. The research method used is descriptive observation method which is carried out by direct observation of objects and explaining them clearly and in detail. From the results of this observation, it was found that obstacles and problems were sourced from human resources as business actors, where limited knowledge and skills in running a business made the business not develop significantly, so the researchers provided suggestions, recommendations and solutions to problems in the form of knowledge and literacy as well as improvement of skills in running a business. In order to maintain business continuity and make the business competitive. in conclusion Knowledge and skills are directly proportional to the ability of MSMEs in running a business which has direct implications for the performance of MSMEs. the more knowledge and skills in running MSMEs, the greater the capacity in running a business so that it can support the performance and productivity of MSMEs.